2022
DOI: 10.7150/jca.71256
|View full text |Cite
|
Sign up to set email alerts
|

LASS2 impairs proliferation of glioma stem cells and migration and invasion of glioma cells mainly via inhibition of EMT and apoptosis promotion

Abstract: LAG1 longevity assurance homolog 2 (LASS2), a highly conserved transmembrane protein, has been reported in several cancer types. However, the roles of LASS2 in glioma biology remain elusive. In the present study, we investigated the expression of LAAS2 in human glioma tissues and the effects of LASS2 on glioma stem cell (GSC) proliferation. Roles of LASS2 in glioma cell migration and invasion were also researched both in vitro and in vivo. Our results demonstrated that the level of LASS2 is gradually reduced w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…Current research and the latest WHO classification standards indicate the value of identifying specific biomarkers for prognosis prediction and treatment. 4,21 The aberrant expression of SERPINH1, a gene encoding for a serine protease inhibitor, is associated with tumor progression due to its role in collagen biosynthesis. 22 Prior research indicated that SER-PINH1 is upregulated in various cancerous growths.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current research and the latest WHO classification standards indicate the value of identifying specific biomarkers for prognosis prediction and treatment. 4,21 The aberrant expression of SERPINH1, a gene encoding for a serine protease inhibitor, is associated with tumor progression due to its role in collagen biosynthesis. 22 Prior research indicated that SER-PINH1 is upregulated in various cancerous growths.…”
Section: Discussionmentioning
confidence: 99%
“…However, the etiopathogenesis of glioma remains unclear. Current research and the latest WHO classification standards indicate the value of identifying specific biomarkers for prognosis prediction and treatment 4,21 …”
Section: Discussionmentioning
confidence: 99%
“…Thus, rQNestin 34.5v2, also a second-generation oHSV, deletes one copy under the control of the nestin promoter simultaneously as the double deletion of the γ134.5 (Nakashima et al, 2015). Nestin is a hallmark molecule in gliomas and is not expressed in other neuronal cells (Zhao et al, 2022). Another mutant that overcomes the insufficient replication capacity of G207 is G47∆, a thirdgeneration oHSV.…”
Section: Oncolytic Herpes Simplex Virus (Ohsv)mentioning
confidence: 99%